Application of existence theorems to asymptotic decompositions - Khoma, L. G. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By the example of a certain nonlinear boundary-value problem for a second-order hyperbolic equation we justify a new approach to the application of the Krylov-Bogolyubov-Mitropolskii asymptoti methods. For certain linear problems, we present the compatibility conditions and the relations enablinj one to construct exact solutions.